The Role Of Digital Marketing In Increasing Customer Satisfaction Of MSME Products (Case Study On Traditional Food Semprong, A Speciality Of Karawang) - Sarip Hidayat; M Yani Syafei; Umi Narimawati (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
Development digital technology has change paradigm marketing , including among Small and Medium Enterprises (SMEs). Digital marketing provides opportunity for SMEs to reach more markets wide , increase interaction , and satisfaction Customers . Research This aiming analyze the role of digital marketing in increase satisfaction customers on products food traditional Squirrel typical of Karawang. The approach used is qualitative with design studies case . Data collected through interview in-depth , observation , and analysis documentation related to digital marketing strategies by craftsmen Semprong Mondy. Research results show that digital marketing strategies, such as social media , websites, and e-commerce, contribute to ease access , quality services , as well as communication between perpetrator business and consumers . Implementation This increase satisfaction customer in matter convenience purchasing and service finished sell . However , there is challenge in the form of limitations source power and competition in the digital world that influences effectiveness of strategy. Research This recommend UKM to more optimizing digital marketing for increase Power competition and satisfaction customer.